Long‐Run Risk: Is It There? - LIU, YUKUN; MATTHIES, BEN (Journal of Finance, 2022)
ABSTRACT This paper documents the existence of a persistent component in consumption growth. We take a novel approach using news coverage to capture investor concern about economic growth prospects. We provide evidence that consumption growth is highly predictable over long horizons—our measure explains between 23% and 38% of cumulative future consumption growth at the five‐year horizon and beyond. Furthermore, we show a strong connection between this predictability and asset prices. Innovations to our measure price 51 standard portfolios in the cross section and our one‐factor model outperforms many benchmark macro‐ and return‐based multifactor models.